1997
DOI: 10.5271/sjweh.217
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative evidence of risk factors for back disorders

Abstract: The scientific literature on work-related back disorders was reviewed to identify consistent rislc factors and to determine the strength of the association between the two. Thirty-five publications were selected with quantitative information. Lifting or carrying loads, whole-body vibration, and frequent bending and twisting proved to be the physical load risk factors consistently associated with work-related baclc disorders. Job dissatisfaction and low job decision latitude proved to be important, but the evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
322
8
12

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(369 citation statements)
references
References 68 publications
27
322
8
12
Order By: Relevance
“…The total lumbar rotation, calculated as the difference between the foregoing two rotations, was subsequently partitioned in between various segments based on values reported in earlier investigations [3,29,34,76,79,91,104]. Relative proportions of~7, 12,15,22,27 and 17% were used to partition the lumbar rotation between various motion segments from T12 to L5 levels, respectively.…”
Section: Prescribed Posturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The total lumbar rotation, calculated as the difference between the foregoing two rotations, was subsequently partitioned in between various segments based on values reported in earlier investigations [3,29,34,76,79,91,104]. Relative proportions of~7, 12,15,22,27 and 17% were used to partition the lumbar rotation between various motion segments from T12 to L5 levels, respectively.…”
Section: Prescribed Posturesmentioning
confidence: 99%
“…Compression force limits have been recommended for safer manual material handling (MMH) maneuvers based on the premise that excessive compression loads could cause injury. Despite the well-recognized role of lifting in low back injuries [4,12,17,33,53], the literature on safer lifting techniques remains controversial [25,48]. In search of optimal lifting methods, squat lift (i.e., knee bent and back straight) is generally considered to be safer than the stoop lift (i.e., knee straight and back bent) in bringing the load closer to the body and, hence, reducing the extra demand on back muscles while counterbalancing the moments of external loads.…”
Section: Introductionmentioning
confidence: 99%
“…Hoozemans and co-workers [15], in their review on pushing and pulling concluded that epidemiological studies provide evidence that pushing and pulling are associated with low back pain when factors such as the load, distance, frequency, handling height, working method and worker characteristics are considered. Looking at the literature, the risk of pushing and pulling has not been studied as well as lifting and carrying, and generally epidemiological data available to answer the question of whether pushing and pulling is related to musculoskeletal complaints is inconclusive [12,57,58].…”
Section: Pushing and Pullingmentioning
confidence: 99%
“…Psychosocial factors have also been associated with both work-and nonwork-related back disorders [9][10][11]. The most frequently reported occupational risk factors are heavy physical work; frequent bending, twisting, lifting, pulling, and pushing; repetitive work; forceful movements; static postures like prolonged sitting, awkward postures and whole-body vibrations [12][13][14][15][16][17][18][19][20][21][22][23]. While the focus of this manuscript is on physical occupational risks, work related psychosocial risk factors that have been identified include anxiety, depression, job dissatisfaction, and mental stress [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Information on specific work-related risk factors is particularly valuable for its preventive potential. For example, unphysiological posture and repetitive carrying, lifting and holding heavy loads are the most conclusively documented work-related risk factors for back pain [7,12,24,42,50,62], although experts disagree as to the specific biomechanical mechanisms of action involved [64]. More in-depth analyses of our data (not presented here) show approximately identical pain scores for 0-7 h of manual labour, and a sharp increase to much higher pain scores for subjects with daily exposure to more than 7 h of heavy manual labour.…”
Section: Socioeconomic Status Risk Factors and Back Painmentioning
confidence: 99%